Clinical Impact of Diabetes Mellitus on Outcomes After Transcatheter Aortic Valve Replacement: Insights From the Society of Thoracic Surgeons/American College of Cardiology Transcatheter Valve Therapy Registry. (November 2017) - Abramowitz, Yigal; Vemulapalli, Sreekanth; Chakravarty, Tarun; Li, Zhuokai; Kapadia, Samir; Holmes, David; Matsouaka, Roland A.; Wang, Alice; Cheng, Wen; Forrester, James S.; Smalling, Richard; Thourani, Vinod; et al.
Abstract : Background—: Diabetes mellitus (DM) adversely affects morbidity and mortality for cardiovascular diseases and procedures. Data evaluating the outcomes of transcatheter aortic valve replacement (TAVR) in diabetic patients are limited by small sample size and contradictory results. We aimed to establish the magnitude of risk and the incremental influence of insulin dependency by examining short- and long-term adverse outcomes according to DM status and therapy in the world's largest TAVR registry. Methods and Results—: We analyzed data from the Society of Thoracic Surgeons/American College of Cardiology Transcatheter Valve Therapy Registry. In-hospital mortality, 30-day mortality, and 1-year mortality after TAVR in patients with and without DM were evaluated using multivariate modeling. Among 47 643 patients treated with TAVR from November 2011 through September 2015 at 394 US hospitals, there were 17 849 (37.5%) patients with DM. Overall, 6600 of the diabetic patients were insulin treated (IT). Thirty-day mortality was 5.0% in patients with DM (6.1% in IT DM and 4.4% in non-IT DM; P <0.001) versus 5.9% in patients without DM ( P <0.001). Overall, 1-year mortality was 21.8% in patients with DM (24.8% in IT DM and 20.1% in non-IT DM; P <0.001) versus 21.2% in patients without DM ( P =0.274). In a multivariable model, DM was associated with increased 1-year mortality (hazard ratio, 1.30; 95% confidence interval, 1.13–1.49; P <0.001). Subgroup multivariable analysis showed stronger mortality association in IT diabetics (hazard ratio, 1.57; 95% confidence interval, 1.28–1.91; P <0.001) than in non-IT diabetics (hazard ratio, 1.17; 95% confidence interval, 1.00–1.38; P =0.052). Conclusions—: Our data establish the magnitude of short- and long-term risk conferred by DM and the incremental risk conferred by insulin dependency in the performance of TAVR. Clinical Trial Registration—: URL:https://www.clinicaltrials.gov . Unique identifier: NCT01737528. Abstract : Supplemental Digital Content is available in the text.